2013
DOI: 10.1016/j.ijid.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

How low can you go? Use of low- and standard-dose liposomal amphotericin B for treatment of invasive fungal infections

Abstract: Comparable rates of clinical improvement, survival to discharge, and toxicity were identified among low- and standard-dose L-AMB recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Compared to dosages of AmB 0.6–0.7 mg/kg/d, dosages of AmB 0.4–0.5 mg/kg/d were not related to increased mortality in CM patients but were related to a lower incidence of adverse effects such as hypokalemia and creatinine elevation. It was noted that a low dosage of AmB (including liposomal AmB) produced more safety and similar efficacy to prevent or treat fungal infections (Koh et al, 2002; Lequaglie, 2002; Kassamali et al, 2013; Yasu et al, 2018). The possible reason that a low dosage of AmB achieved comparable efficacy to a standard dosage of AmB may be that first, AmB is a fungicidal medicine with a long half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to dosages of AmB 0.6–0.7 mg/kg/d, dosages of AmB 0.4–0.5 mg/kg/d were not related to increased mortality in CM patients but were related to a lower incidence of adverse effects such as hypokalemia and creatinine elevation. It was noted that a low dosage of AmB (including liposomal AmB) produced more safety and similar efficacy to prevent or treat fungal infections (Koh et al, 2002; Lequaglie, 2002; Kassamali et al, 2013; Yasu et al, 2018). The possible reason that a low dosage of AmB achieved comparable efficacy to a standard dosage of AmB may be that first, AmB is a fungicidal medicine with a long half-life.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ellis et al reported a prospective randomized trial that compared the efficacy of two dosages of L-AMB for treatment of invasive aspergillosis and found that a daily dose of 1 mg/kg was as effective as a dose of 4 mg/kg (10). Moreover, although the optimal dose of L-AMB for empirical or preemptive therapy during neutropenia remains unclear, several prospective and retrospective studies have suggested that a daily dose of L-AMB as low as 1 mg/kg is effective for empirical therapy and for prevention of IFIs during neutropenia (9)(10)(11)(12)(13)(14). Among those studies, Prentice et al reported a prospective randomized trial that compared the efficacy of two dosages of L-AMB and conventional D-AMB for empirical therapy during neutro- penia and found that a daily dose of L-AMB of 1 mg/kg could provide an efficacy similar to that of 3 mg/kg L-AMB (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although L-AMB has a significantly improved toxicity profile, compared with conventional amphotericin B deoxycholate (D-AMB), adverse events such as hepatotoxicity, nephrotoxicity, electrolyte abnormalities, and infusion-related reactions also frequently occurred with recommended daily doses of L-AMB ranging between 3 and 6 mg/kg (3,4). However, recent studies have suggested that low doses of L-AMB (less than ϳ2 mg/kg/day) are effective and have less toxicity for patients with hematological malignancies (9)(10)(11)(12)(13)(14). Therefore, the optimal daily dosage of L-AMB is controversial.…”
mentioning
confidence: 99%
“…However, because they used effectiveness measures from the study by Walsh et al (26), who only used doses of 3 mg/kg, cost-effectiveness analysis was not possible. The use of low doses of LAmB has been evaluated, and most studies indicate that there is no significant improvement in major outcomes with higher doses (32)(33)(34)(35). Therefore, conducting economic evaluations based on studies that used low doses of L-AmB (1-2 mg/kg) could provide a new perspective in the pharmacoeconomics of LAmB.…”
Section: Discussionmentioning
confidence: 99%